PENENTUAN NILAI OPSI ASIA PADA KOMODITAS BAWANG MERAH DENGAN MENGGUNAKAN METODE MONTE CARLO - Rosydatul Muawanah Rosy; Fitroh Resmi; Krisna Adilia Daniswara (MathVisioN, 2023)
Shallot is a commodity that is needed in everyday life. However, the uncertainty of the price of shallots makes farmers suffer losses. This uncertainty can be overcome by using options on the sale of shallots. The Asian option was chosen because it is cheaper than the other options. To determine the value of this Asian option, the commodity price return model is used. The method that fits this model is the Monte Carlo method. In this study, data on shallot commodity prices were taken on the website of the National Strategic Food Price Information Center (PIHPS Nasional) in traditional markets in Surabaya for 4 years. The research of this study indicate that when the strike price is more than the initial shallot price , then the Asian put option price is higher. Meanwhile, when the strike price is less than the initial shallot price , the price of the Asian put option is low.